Efficacy of potato resistant starch prepared by microwave–toughening treatment. (15th July 2018) - Li, You-Dong; Xu, Tong-Cheng; Xiao, Jun-Xia; Zong, Ai-Zhen; Qiu, Bin; Jia, Min; Liu, Li-Na; Liu, Wei
Highlights: Resistant potato starch was prepared using a microwave–toughening treatment (MTT). As-prepared resistant potato starch was strongly digestion resistant. MTT significantly improved the crystalline performance and heat resistance. Resistant starch controlled the postprandial blood sugar in mice. Fasting blood sugar, body weight, and organ index in mice were also improved. Abstract: Potato starch was treated by microwaving, toughening, and low-temperature aging to prepare resistant starch (RS). The functional properties of the resultant RS were evaluated and the effects of this microwave–toughening treatment (MTT) on the amylose content, RS content, digestive properties, pasting properties, morphological observation, crystal structure, and thermal performance of potato starch were determined. The optimal MTT parameters were microwaving at 300 W for 100 s, toughening at 55 °C for 16 h, and low-temperature aging at 4 °C for 18 h. After MTT, the amylose and RS contents of potato starch had increased from 26.08% and 11.54% to 35.06% and 27.09%, respectively. Furthermore, the pasting temperature increased from 66.8 °C to 76.36 °C, while the peak viscosity, trough viscosity, and final viscosity decreased significantly. After MTT, the potato starch surface had also changed significantly, and the crystallinity had increased from 32.43% to 51.36%. MTT starch had beneficial effects on fasting blood glucose, body weight, and organ index in mice. Furthermore, it had a protective effect on subcutaneous abdominal fat and liver tissue.